Introduction the New Indigenous Subject Guide. - Carpenter, Brian; Sutherland, Paul (Transactions of the American Philosophical Society, 2024)
The article discusses the launch of a new Guide to Indigenous Materials at the American Philosophical Society Library, developed by the APS and its Center for Native American and Indigenous Research (CNAIR). This comprehensive guide covers a vast archival collection related to the languages, cultures, and histories of Indigenous peoples of the Americas, dating from 1553 to 2023, and includes over five hundred different Indigenous cultures and languages. The guide features a user-friendly interface for searching and locating materials, incorporates updated terminology to reflect contemporary usage, and acknowledges Indigenous authorship and expertise. It also highlights ongoing efforts to improve the guide and expand its content, ensuring it serves as a valuable resource for researchers.